Pembuatan formulasi ektrak kulit batang Calophyllum soulattri dan aktivitas residu terhadap larva Crocidolomia pavonana - Edy Syahputra; Djoko Prijono (Jurnal Entomologi Indonesia, 2008)
One option to lessen the problems arising from the use of synthetic insecticides is to exploit plants that have insecticidal activities, such as species of Calophyllum(Clusiaceae). The study has been conducted to prepare insecticidal formulation from C. soulattri bark extract and to evaluate their residual activity against C. pavonana. Formulation prepared by using emulsifier, solvent, and sticking agent. Colour, acidity and emulsion stability were recorded as physic-chemical character of formulation. The result showed that the formulation of C. soulattri bark extract was stable, and their pH was normal. Bioassay of residual activity was done using leaf-residual method. Formulation of bark extract of 66 EC sprayed in suspension concentration of 1% on potted broccoli plant had residual activity around 70.7%-72% with range of half-lives of 9.4-9.6 days.